1988
DOI: 10.1007/bf01420767
|View full text |Cite
|
Sign up to set email alerts
|

Synergisms in binary surfactant mixtures

Abstract: Significant correlations become apparent between synergisms of micelle formation in surfactant mixtures and a series of physico-chemical properties and applications. Examples are emulsifying, dispersing, wetting, flotation, washing and cleaning ability. As a result, the effect of a co-surfactant with respect to problems of application can be predicted by a few surface tension measurements only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
6

Year Published

1992
1992
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 12 publications
(13 reference statements)
0
50
0
6
Order By: Relevance
“…Mixtures of different surfactant types often exhibit synergism in their effects on the properties of the system (6)(7)(8)(9)(10)(11)(12)(13)(14). The observed synergism can be attributed to nonideal mixing effects in the aggregates, and results in substantially lower CMCs and interfacial tensions than would be expected based on the properties of the unmixed surfactants alone.…”
Section: General Description Of Mixed Surfactant Solutionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mixtures of different surfactant types often exhibit synergism in their effects on the properties of the system (6)(7)(8)(9)(10)(11)(12)(13)(14). The observed synergism can be attributed to nonideal mixing effects in the aggregates, and results in substantially lower CMCs and interfacial tensions than would be expected based on the properties of the unmixed surfactants alone.…”
Section: General Description Of Mixed Surfactant Solutionsmentioning
confidence: 99%
“…The observed synergism can be attributed to nonideal mixing effects in the aggregates, and results in substantially lower CMCs and interfacial tensions than would be expected based on the properties of the unmixed surfactants alone. This situation has lead to both theoretical and practical interest in developing a quantitative understanding of the behavior of mixed surfactant systems, and can be exploited in applications such as detergency (14)(15)(16), enhanced oil recovery (17) and mineral flotation (18). We begin with the topic of mixed micelles, since monomer-micelle equilibrium exerts a key controlling influence on the behavior of the overall mixed surfactant system.…”
Section: General Description Of Mixed Surfactant Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mixtures of different surfactant types always found to have lowerCMCs and interfacial tensions than would be expected based on the properties of the pure surfactants. 22 This situation leads to an increase in both theoretical and practical interest in developing a quantitative understanding of mixed surfactant behavior, and couldbe exploited in applications such as detergency, 23 enhanced oil recovery 24 and mineral flotation. 25 However, it is found that the correlation between the ability of a surface-active compound to lower surface tension and its ability to prevent microbial adhesion.…”
Section: Resultsmentioning
confidence: 99%
“…Ми вважаємо, що на межі поділу фаз рідина-рідина вуглеводневі радикали молекул ПАР розташовані не зовсім перпендикулярно площині кордону розділу фаз, а переплі-таються між собою, що добре узгоджується з відомими літературними даними [13].…”
Section: рис 1 ізотерма поверхневого натягу нпав (1) та апав (2)unclassified